Effect of proton pump inhibitors on occlusion of lumen-apposing metal stents and rate of endoscopic necrosectomies: a Europe-wide multicenter cohort study - Hamm, Jacob; Busana, Alzbeta; Amanzada, Ahmad; Arlt, Alexander; Asendorf, Thomas; Carswell, Samantha; Denzer, Ulrike; Elsing, Louis; Frost, Fabian; Guilabert, Lucia; Hamesch, Karim; Hollenbach, Marcus; et al. (Endoscopy, 2025)
Lumen-apposing metal stents (LAMS) are widely used to drain walled-off necrosis (WON). LAMS occlusion is a significant clinical problem and identification of risk factors for LAMS occlusion could contribute to novel preventive strategies. A previous study suggested contradictory effects of proton pump inhibitors (PPIs) on occlusion and necrosectomy rates.